The situation of HIV-1 antiretroviral drugs resistance in Pranangklao Hospital - Phadungpattanodom, Jariya (Journal of Medical and Public Health Region 4, 2020)
The number of HIV infected persons receiving antiretroviral (ARV) therapy increases every year. In order to change ARV regimen, the doctor will request HIV drug resistance testing for diagnosis of treatment failure. This study was to determine the information of ARV resistance rate, gene mutation, and the number of ARV hypersensitivity gene at Pranangklao Hospital. The population target was 2,478 HIV infected patients with HIV viral load testing during January 2017 to December 2018. Among these, the age of HIV infection and resistance to ARV drugs were age group between 30-49 years old. One hundred twenty-eight cases (5.2%) had the amount of virus in plasma >1000 copies/ml which were 61 male (47.7%) and 67 females (52.3%). There were 103 cases (4.2%) who developed ARV drug resistance. Nucleoside/nucleotide Reverse Transcriptase Inhibitors (NRTIs) resistance mutations were found in 79 patients with M184V (77.2%) cause resistance to emtricitabine and lamivudine 65 patients. Thymidine Analog Mutations (TAMs) in 6 positions include M41L, D67N, K70R, L210W, T215F and K219R were found about 10.1,17.7,11.4, 3.8, 8.9 and 3.8%, respectively. Non-Nucleoside/nucleotide Reverse Transcriptase Inhibitors (NNRTIs) resistance mutations were found in 90 patients with K103N (51.1%), and secondly Y181C (25.5%) which cause resistance to nevirapine and efavirenz in 85 and 73 patients, respectively. There were 62 patients with resistance to both classes of NNRTIs and NRTIs where as 3 patients had resistant to Protease inhibitors (PIs). The gene polymorphisms were most commonly found at positions of M36I, H69K and L89M which not resistance to PI mutations. Among 115 HIV infected persons, HLA-B*5701 or abacavir hypersensitivity gene were found in 5 cases (4.3%). To monitor ARV resistance, CD4, HIV viral load and drug resistance testing are the most effective follow up. People infected with HIV who receive abacavir should have HLA-B* 57:01 screening to prevent serious drug hypersensitivity.